Evaluation of errors in estimating the azimuth of powerful lightning discharges from measurements of Q-bursts - Shvets, A.; Budanov, O.; Koloskov, O.; Nickolaenko, O.; Shvets, O.; Yampolsky, Yu. (Ukrainian Antarctic Journal, 2021)
In this work, we study the variability of errors in determining the azimuth of Q-bursts’ sources on a daily time scale. Q-bursts are electromagnetic pulse radiation in the extremely low frequency (ELF) range, excited by powerful lightning discharges, and they are used to locate lightnings over the world. We estimated the errors from data collected for two horizontal orthogonal magnetic field components of Q-bursts. Experimental records of Q-bursts were made at Akademik Vernadsky station from March to April 2019, which covers the vernal equinox day. We determined the azimuth of a Q-bursts’ source by digital rotation of the coordinate system until the signal in one magnetic component would drop to its minimum value. The absolute value of the azimuth error was estimated from the ratio of the Q-burst’s amplitude to the standard deviation of the residual signal. With an automated processing procedure, we analyzed over 800 thousand Q-bursts with amplitude over 10 picotesla. A characteristic diurnal pattern has been discovered in the estimated azimuth errors variations. The night level of the azimuth error exceeded the day level by about two degrees on average. The decrease-rise-decrease И-shaped swing during transition from night to day and mirror-symmetric N-shaped swing during transition from day to night were identified. Each of those transitional swings takes about four hours. A comparison of the daily variations in the total intensity of ELF background noise with the estimated daily azimuth error diagrams demonstrates the opposite character: maximal level of the ELF background noise was observed during the daytime while the estimated azimuth errors take minimal values at this time. This contradicts the generally accepted notion that increasing the noise increases the error. Thus, we suppose that the residual magnetic component in a Q-burst occurs not only from the background noise but can also result from nonlinear polarization of the incident wave due to gyrotropy of the nighttime lower ionosphere. Coherent waves resulting from diffraction of the incident field on the day-night interface in the Earth-ionosphere cavity could explain the И- and N-shaped swings of the azimuth error during the passage of the solar terminator.